HUBUNGAN TINGKAT STRES PANDEMI COVID-19 DENGAN PERILAKU KOMPULSIF TERKAIT KEBERSIHAN PADA SISWA SMA NEGERI KOTA 1 BOGOR TAHUN 2022 - Muhammad Irfaan Yaafi (2022)
Covid-19 pandemic which has been lasted for more than two years with a very high number of positive cases and deaths, has caused prolonged stress and anxiety in the community. The 5M health protocol requires the public to always maintain personal and environmental hygiene to suppress the spread of Covid-19. Various studies that have been conducted previously show that prolonged stress is one of the triggering factors for the development of OCD (Obsessive Compulsive Disorder) in individuals who have OCD tendencies and can worsen the OCD symptoms (compulsive behavior) in OCD sufferer. This study aims to determine the relationship between covid-19 pandemic stress level and compulsive cleaning behavior in students of SMA Negeri 1 Kota Bogor in 2022. This study used an observational analytical design with a cross-sectional method using the validated Perceived Stress Scale (PSS-10) and validated Yale-Brown Obsessive Compulsive Scale (Y-BOCS). Sampling of 49 respondents with age ranges from 16 to 18 years was carried out by the simple random sampling method which then analyzed by the Chi-Square test. The study shows the majority of students experienced low to moderate stress level. There is a relationship between Covid-19 pandemic stress level and compulsive cleaning behavior in students of SMA Negeri 1 Kota Bogor in 2022 (p = 0.00). Compulsive cleaning behavior is more common in students with moderate (20.41) to high (26.53) stress level during Covid-19 pandemic (OR 28.364; CI 3.286-244.844).